Challenges in Bilingual Teaching among Teachers of Teacher Education Institutions of Punjab - Hussain, Shamim Aara; Singh, Varinder (Voices of Teachers and Teacher Educators, 2021)
The teacher, the most vital element who can maximise learning outcomes of students, gets overlooked. Teachers hold a key position in any educational reconstruction programme. Various research, education commissions and policies have elaborated the effectiveness of learner-centered instruction, especially mother tongue-based education. It is also recommended to adopt bilingual approach in teaching learning process. But only limited empirical research has looked deeply at challenges faced by teachers especially in bilingual classrooms. Therefore, it is quite important to know whether content teachers are adequately prepared to address the rising number of bilingual students in their classrooms. To find out the challenges in bilingual teaching among teachers of teacher education institutions, researchers constructed an online five-point rating scale with 26 positive and negative items related to challenges in bilingual teaching. The sample consisted of 28 male and female teachers of different teacher education institutions of Punjab. Descriptive analysis was used to describe the basic features of the data and to provide simple summaries about the sample. After analysing the received data, it was found that most participants agreed that they get very little support from the administration regarding bilingual teaching; half the participants admitted that they have difficulty with technical terms and academic vocabulary in two languages during the lecture; most participants felt the lack of quality learning resources like books in both languages; and more than half the teachers admit that they face difficulties in using ICT while preparing lesson plans and providing instruction in a language other than English (as ICT generally supports only English language). It is recommended that there should be pre-service and in-service teacher training programmes that can sensitise the teachers to deal with bilingual situations in an academic environment. Such training programmes must equip teachers with strategies that can be used to tackle the bilingual or multilingual classroom situations. Also, developing, applying, and sustaining a bilingual educational programme demands leaders who are attentive about bilingualism, bilingual education, bilingual teaching, and emergent bilingual student population. Moreover, there is need to encourage the publishers to produce authentic study materials in different language for immediate use. In addition to this, research in the field of bilingual or multilingual education must be supported and promoted so that various solutions can be drawn to deal with challenges concerned with bilingual teaching.